EFEKTIVITAS PENDIDIKAN KESEHATAN DENGAN METODE AUDIOVISUAL TERHADAP PERILAKU SISWA TENTANG JAJANAN YANG SEHAT DAN AMAN PADA ANAKKELAS 4 DAN 5 DI SDN SRONDOL WETAN 06 BANYUMANIK SEMARANG - Eliana Saputri; Elis Hartati; Mutia Galuh (Jurnal Ilmu Keperawatan Komunitas, 2018)
School-aged children are food consumers . They actively and independently decide food they want to consume, whether school snacks or other snacks sold in other places. There are various diseases that can be occurred related with unhealthy snacks; they are diarrhea with 30.001 cases and diphtheria with 2 cases. The survey that was conducted in elementary schools of Banyumanik municipality Semarang showed the level of behaviours in choosing healthy and safe snacks is still low. One of efforts in forming school-aged children’s behaviors is conduct the health education. To improve the children’s behaviors, audiovisual method is used as it is easy to understand by school-aged children. The search is aimed to determine the effectiveness of health education using audiovisual method on students’ behaviors toward healthy and safe school snacks of grade 4 and 5 children at Srondol Wetan 06 Elementary School Banyumanik Semarang. This research uses quasi experiment design with pre and post test without control design. There are 103 respondents as samples. They are collected using random sampling method. Thos research also using Wilcoxon statistic examination. Based on the result of the statistic exanination, it can be concluded that there is an determined p-value of 0,000 (p-value <  0,05). It can be concluded that there is an effectiveness of health education using audiovisual method on  students’ behaviors towards health and safe school snacks of grade 4 and 5 children at Srondol Wetan 06 Elementary School Banyumanik Semarang. This research suggest that the school should make a program of healthy and clean canteen. The school should also monitor the students’ behavirs in choosing healthy and safe snacks so that it becomes a good habit and culture for the students.